(untitled) (Journal of Forensic Medicine & Toxicology, 2017)
Hanging has been employed as the method of suicide since time immemorial and is described as a painless death. There is need to study vital demographic parameters with respect to hanging as it an important social issue.The present study is a cross sectional study conducted on the dead bodies of either sex brought for medico legal autopsy with the history of death due to hanging in the Department of Forensic Medicine and Toxicology at a Medical College in Central India from 1st August 2011 to 31st July 2017. During the study period 101 cases of hanging are studied. It is analyzed thatthe majority (81.18%) of hanging cases belong to the rural area while the 14.85% of cases belong to the urban area and the majority of victims (71.28%) died during the month of March to September with a peak of 14.85% in month of May.